DIRECTIONS FOR DEVELOPING INNOVATIVE ENTREPRENEURSHIP TO INCREASE POPULATION INCOME: https://doi.org/10.5281/zenodo.16736863 - Ergasheva , Nafisa (Science technology&Digital finance, 2025)
This article analyzes the issues of development of innovative entrepreneurship as an important means of sustainable increase of income of the population. The role of innovative entrepreneurship in economic growth, its impact on socio-economic stability and Current Directions are covered on a scientific basis. Also, in the conditions of Uzbekistan, the possibilities of increasing income on the basis of innovative ideas were discussed.